TLR7 Deficiency Leads to TLR8 Compensative Regulation of Immune Response against JEV in Mice - Awais, Muhammad; Wang, Ke; Lin, Xianwu; Qian, Wenjie; Zhang, Nan; Wang, Chong; Wang, Kunlun; Zhao, Ling; Fu, Zhen F.; Cui, Min (Frontiers in Immunology, 2017)
Japanese encephalitis virus (JEV) is a highly fatal pathogen to human beings. Toll like receptor 7 (TLR7) plays a role as first host defense against most ssRNA flaviviruses. This study aims to investigate the role of TLR7 in inducing adaptive immune response in mice against Japanese encephalitis virus. In vitro and in vivo study was conducted to examine the expression of TLRs in mice. After JEV infection, physical parameters of mice (Survival rate and body weight) were evaluated and organs or cell were collected for further analysis. TLR7 expression was increased significantly as compare to other TLRs post JEV infection. CD80, CD86 and CD273 cells expression on bmDC cells was increased significantly in TLR7-/- mice. Furthermore viral load was also increased significantly in TLR7-/- mice as compare to C57BL/6 mice. But there was no significant difference among survival rate and body weight in TLR7-/- mice as compare to C57BL/6. Interestingly, we also found that TLR8 was up-regulated in TLR7-/- mice. The study concluded that TLR8 was up-regulated in TLR7 deficient mice and it might play a compensatory role in the immune response in TLR7-/- mice.